Pelatihan Pembuatan Video Pembelajaran Menggunakan Aplikasi Kinemaster untuk Guru di SMAN 6 Kediri - Zainal Afandi; Yatmin Yatmin; Agus Budianto; Heru Budiono; Sigit Widiatmoko; Nara Setya Wiratama; Siska Nurazizah Lestari; Alkari Alkari; Ferry Ferdian (Universitas Pahlawan Tuanku Tambusai, 2022)
Kinemaster is one of the best video editor apps for Android. This is because the features are complete and easy to understand, and do not require a smartphone with high specifications. This PkM activity aims to provide training to teachers in making interesting and fun learning videos using the Kinemaster application at SMA Negeri 6 Kediri. The method used in this community service is a training method consisting of the stages of planning (observation), implementation (lectures, discussions, demonstrations), and evaluation. Based on the evaluation of the results of the implementation, of the 20 participants who attended the training, 17 people successfully completed their assignments and were very satisfied, while 3 participants had some problems due to the age factor. In addition, participants gain new skills in making learning videos, which can be made anywhere without having to face a computer. Based on these results, it can be concluded that the PkM activities carried out were achieved.